Research on Key Strategies of 3G/4G Convergence Network - Fei Zhou (Dianxin kexue)
With release of TD-LTE license in China, how to deploy LTE becomes the primary problem for network operators. Techniques of both WCDMA and LTE network were analyzed in detail, and LTE construction thoughts of China Unicom were elaborated from the viewpoints of brand convergence, network convergence and mobile terminal convergence, which aimed to promote combination of 3G and 4G to fulfill the best mobile broadband network.